1989
DOI: 10.1007/bf00788172
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a highly nuclease resistant RNA fragment in prosomes

Abstract: Prosomes, small cytoplasmic particles of mouse erythroblasts were found to contain low molecular weight RNA molecules in the range of 80 nucleotides. Nuclease digestion of prosomes suggests that prosomal proteins cover and protect almost the whole length of their RNA(s). Our results demonstrate clearly that RNA is an intrinsic component of prosomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1990
1990
1997
1997

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Isolation of the particle by different purification procedures systematically led to copurification of small RNA species with the prosome-MCP particle. Furthermore, Dineva and co-workers [15] showed that most of the prosomal RNA is digested by nucleases only after phenol extraction, i.e. after elimination of the prosomal proteins.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Isolation of the particle by different purification procedures systematically led to copurification of small RNA species with the prosome-MCP particle. Furthermore, Dineva and co-workers [15] showed that most of the prosomal RNA is digested by nucleases only after phenol extraction, i.e. after elimination of the prosomal proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the protection of prosomal RNA against nuclease digestion by intact and Zn2+-dissociated prosomal particles To test stringently the controversial question about the presence of RNA in the particle, we took advantage ofthe dissociation of the particle on Zn2+ treatment. Dineva and co-workers [15] gave evidence for high nuclease resistance of 80-90 % of the RNA in the intact prosomes. Taking this result as a basis, we addressed the question as to whether the pRNA could be digested by nuclease after dissociation of the complex into its protein subunits by Zn2+.…”
Section: Analysis Of the Dissociated Protein Subunitsmentioning
confidence: 99%
See 1 more Smart Citation
“…The individual particle has a defined morphological and biochemical structure (12 -17 nm in the electron microscope, z 720 kDa) and is made up of about 15 proteins with total molecular mass of 19 -36 kDa (Coux et al, 1992). Prosomes also contain several small RNAs 80 -120 nucleotides long (Schmid et al, 1984;Martins de Sa et al, 1986); this RNA (pRNA) is an intrinsic part of the complex, as shown by nuclease digestion assays, where over 80% of the length of the RNA was found to be protected (Dineva et al, 1989). Furthermore, prosomal RNAs inhibit, similarily to intact particles, in vitro protein synthesis and hybridize stably to mRNA (Martins de Sa et al, 1986;Horsch et al, 1989).…”
mentioning
confidence: 99%
“…Therefore, in the light of these observations, it was suggested that these RNA species, in conjunction with proteasomes, play a role in the processing of RNA (Arrigo et al, 1985). Since it was shown that the protein-bound RNA species are nuclease resistant and that their digestion is only possible by initially digesting the proteasomal protein components, it was concluded that these RNAs must be fully protected by the proteasome particle (Dineva et al, 1989).…”
mentioning
confidence: 99%